2003
DOI: 10.1074/jbc.m209898200
|View full text |Cite
|
Sign up to set email alerts
|

Taurolithocholic Acid Exerts Cholestatic Effects via Phosphatidylinositol 3-Kinase-dependent Mechanisms in Perfused Rat Livers and Rat Hepatocyte Couplets

Abstract: Taurolithocholic acid (TLCA) is a potent cholestatic agent. Our recent work suggested that TLCA impairs hepatobiliary exocytosis, insertion of transport proteins into apical hepatocyte membranes, and bile flow by protein kinase C⑀ (PKC⑀)-dependent mechanisms. Products of phosphatidylinositol 3-kinases (PI3K) stimulate PKC⑀. We studied the role of PI3K for TLCA-induced cholestasis in isolated perfused rat liver (IPRL) and isolated rat hepatocyte couplets (IRHC). In IPRL, TLCA (10 mol/liter) impaired bile flow b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
89
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 44 publications
12
89
1
Order By: Relevance
“…The anticholestatic bile acid, TUDCA, reversed the effect of TLCA on Bsep density in canalicular membranes and mediated insertion of Bsep into canalicular membranes of cholestatic rat liver along with stimulation of bile flow, vesicular exocytosis, and organic anion secretion in the same experimental model as reported recently. 7,8 These data complement and corroborate our previous immunoelectronmicroscopic findings which showed that TUDCA stimulates insertion of another key apical carrier, the conjugate export pump, Mrp2, into its target membrane in bile acid-induced cholestasis. 7 Bile acids and Mrp2 substrates such as glutathione conjugates represent the major driving forces of bile formation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The anticholestatic bile acid, TUDCA, reversed the effect of TLCA on Bsep density in canalicular membranes and mediated insertion of Bsep into canalicular membranes of cholestatic rat liver along with stimulation of bile flow, vesicular exocytosis, and organic anion secretion in the same experimental model as reported recently. 7,8 These data complement and corroborate our previous immunoelectronmicroscopic findings which showed that TUDCA stimulates insertion of another key apical carrier, the conjugate export pump, Mrp2, into its target membrane in bile acid-induced cholestasis. 7 Bile acids and Mrp2 substrates such as glutathione conjugates represent the major driving forces of bile formation.…”
Section: Discussionsupporting
confidence: 81%
“…The exact molecular mechanism by which TUD-CA stimulates exocytotic fusion of vesicles at the apical membrane 7,25 and apical carrier insertion 7,12,13 remains elusive. Various signaling molecules including isoforms of PKC, 7,9,13 cytosolic-free calcium (Ca 2 þ ) i , 9,25 mitogen-activated protein (MAP) kinases p38 MAPK6,12,13 and p44/42 MAPK , 11,14 src kinase 6 as well as PI3K 8,[26][27][28] have been shown to be involved in bile acid-dependent hepatobiliary exocytosis and carrier insertion/retrieval in apical membranes under various experimental conditions. 29 In the normal rat liver, TUDCA may trigger insertion of Bsep into canalicular membranes by a dual integrin-dependent signaling pathway which includes activation of p44/42 MAPK on one hand and activation of p38 MAPK on the other hand 6,[11][12][13] Preliminary evidence suggests that this pathway may be less relevant for the anticholestatic effect of TUDCA in bile acid-induced cholestasis 14,15 In TLCA-induced cholestasis, the anticholestatic effect of TUDCA appears to be mediated in part by PKC-dependent mechanisms although the exact isoform involved has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonhepatic cells, cAMP can activate Src-TYK (30), and Src-TYK are known to upregulate PI3K/Akt signaling (2,9,38,39,48). In addition, Src-TYK are well-known prosurvival signaling molecules in many cell types including hepatocytes (5,14,44,55). Thus Src-TYK may also be involved in cAMP-GEF-mediated cytoprotection and PI3K activation in hepatocytes.…”
mentioning
confidence: 99%
“…For example, transcription of Mrp2 is downregulated in cholestatic liver diseases (41), and Mrp2 is retrieved from the canalicular membrane during cholestasis induced by taurolithocholate (TLC) (2) or estradiol-17␤-glucuronide (E 2 17G) (25). The TLC-induced retrieval of Mrp2 may be mediated via a phosphoinositide-3-kinase (PI3K)/PKC⑀-dependent mechanism (3). Taurocholate (TC), tauroursodeoxycholate (TUDC), and cAMP, on the other hand, increase biliary excretion of Mrp2 substrates and induce Mrp2 translocation to the canalicular membrane (2,9,33), and cAMP can reverse E 2 17G-induced retrieval of Mrp2 (25).…”
mentioning
confidence: 99%